2008
DOI: 10.1016/j.ydbio.2008.04.037
|View full text |Cite
|
Sign up to set email alerts
|

An absence of Twist1 results in aberrant cardiac neural crest morphogenesis

Abstract: The basic helix-loop-helix transcription factor Twist1 plays an essential role in mesenchymal cell populations during embryonic development and in pathological disease. Remodeling of the cardiac outflow tract (OFT) into the functionally separate aortic arch and pulmonary trunk is dependent upon the dynamic, coordinated contribution of multiple mesenchymal cell populations. Here, we report that Twist1(-/-) mice exhibit OFTs that contain amorphic cellular nodules within their OFT endocardial cushions. The nodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 55 publications
4
83
1
Order By: Relevance
“…When TWIST1 persists at later stages of valve development, it leads to increased mesenchyme proliferation, increased TBX20 expression, and primitive ECM (Chakraborty et al, 2010b). TWIST1 directly regulates Tbx20 (Lee and Yutzey, 2011), but, of note, Twist1-null hearts do not show a difference in Tbx20 levels in the AVC compared with WT (Vincentz et al, 2008). Interestingly, we found that TBX20 was downregulated in the Sox9 cKO AVC and that SOX9 occupied regulatory regions associated with TBX20.…”
Section: Sox9 Modulates the Transcript Levels Of Key Tfs In Heart Valmentioning
confidence: 62%
See 1 more Smart Citation
“…When TWIST1 persists at later stages of valve development, it leads to increased mesenchyme proliferation, increased TBX20 expression, and primitive ECM (Chakraborty et al, 2010b). TWIST1 directly regulates Tbx20 (Lee and Yutzey, 2011), but, of note, Twist1-null hearts do not show a difference in Tbx20 levels in the AVC compared with WT (Vincentz et al, 2008). Interestingly, we found that TBX20 was downregulated in the Sox9 cKO AVC and that SOX9 occupied regulatory regions associated with TBX20.…”
Section: Sox9 Modulates the Transcript Levels Of Key Tfs In Heart Valmentioning
confidence: 62%
“…TFs with the most reduced expression in Sox9 cKO valves were Twist1, Sox4 and Mecom. Similar to SOX9, these three TFs are highly expressed in the cardiac cushions and mutations in each of these factors cause major valve defects, resulting in embryonic fatality (Ya et al, 1998;Vincentz et al, 2008;Bard-Chapeau et al, 2014).…”
Section: Sox9 Modulates the Transcript Levels Of Key Tfs In Heart Valmentioning
confidence: 99%
“…Etv expression patterns overlap with Twist1 in several other developing tissues, such as the somites, cardiac mesenchyme, pharyngeal and branchial arches (Fuchtbauer, 1995;Chotteau-Lelievre et al, 2001;Brent and Tabin, 2004;Vincentz et al, 2008). Furthermore, the expression of both Etv and Twist1 is upregulated in breast cancer cells (Baert et al, 1997;Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Digoxygenin (DiG)-labeled section and whole-mount ISHs were carried out as described (Barnes et al, 2011;Firulli et al, 2010;Vincentz et al, 2008). qRT-PCR was performed on a LightCycler 480II (Roche) using TaqMan primers (Life Technologies) recognizing the following transcripts: Fgf8, Spry1, Fgfr1, Etv5, Etv4, Shh, Ptch1, Gli1, Gli3 and Twist1.…”
Section: Ish-qrt-pcrmentioning
confidence: 99%